Targeting the latent cytomegalovirus reservoir with an antiviral fusion toxin protein - B. A. Krishna; K. Spiess; E. L. Poole; B. Lau; S. Voigt; T. N. Kledal; M. M. Rosenkilde; J. H. Sinclair (Nature Communications, 2017)
Reactivation of human cytomegalovirus in immunosuppressed transplant patients can cause severe complications. Here, Krishnaet al. show that a fusion toxin protein that specifically binds the viral surface protein US28 can be used to kill latently infected monocytes and their progenitor cells in vitro.